Budaya Patriarki dalam Suku Batak Toba Terhadap Hak dan Kedudukan, Tradisi, Peran Gender, dan Perubahan Sosial - Mikha Valdo Tonggo Tambunan; Sihotang , Yulia Fanissah (Yayasan Tri Edukasi Ilmiah, 2025)
The patriarchal culture within the Batak Toba society has a significant influence on women’s rights and status, gender roles, and social change. The patrilineal system adopted by the Batak Toba community positions men as the primary heirs within the family and customary structures, while women hold more limited roles in inheritance and decision-making. This study employs a descriptive qualitative approach to analyze how patriarchal culture persists and how modernization and awareness of gender equality affect social dynamics in Batak Toba society. Using Beauvoir’s feminist theory (1949) and the theory of social construction of gender (Sibarani, 2020), the study finds that although patriarchal norms remain strong, there has been a shift in women’s access to education, employment, and public roles. Women are increasingly involved in family decision-making and have begun to gain inheritance rights, although still in smaller portions compared to men. These findings indicate that the customs and culture of the Batak Toba society are dynamic and evolving in line with the changing times and the growing awareness of gender equality. This transformation reflects a shift in the social structure and cultural values of the Batak Toba people toward a more equitable and gender-just society.